Investigation of glass bubbles im16k polyamide 12 composites for selective laser sintering - Klett, James; Osswald, Tim A.; Cholewa, Simon (Annual Technical Conference - ANTEC, Conference Proceedings, 2020)
Selective Laser Sintering is an additive manufacturing technique that has been increasingly exploited in small-batch production to supplement traditional polymer processing techniques. Integrating specialized additives with PA 12 SLS powder allows for the production of parts with tailored properties. 3M™ Glass Bubbles 1MI6K offers the possibility to reduce SLS powder cost, reduce part weight, and improve mechanical performance. Both intrinsic and extrinsic properties and their effects on SLS processing have been investigated. Tensile testing revealed the average Young's modulus could be improved by 30% at 5 wgt% loadings, while maintaining ultimate tensile strength.
CRIS-Team Scopus Importer:2021-04-19